Police and the society - Earayil, Alphonse L.; Vadackumchery, James (Trivandrum, Kerala, India : Kairali Books International, 1985)
Study based on data collected from Kerala.
Includes index.
Bibliography: p. [xxxvii]-xliii.
Amirul
Keywords: Police-community relations -- India -- Kerala; Police -- India -- Kerala